THE EVOLUTION OF THE ENGLISH LANGUAGE OVER TIME (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Over the ages, social, political, and cultural influences have had a considerable impact on the English language. This study looks at how English has changed throughout time, from its earliest usage to its current position as a univeral language. Old English, Middle English, Early Modern English, and Contemporary English are among the significant changes that we examine using linguistic and historical techniques. The findings demonstrate how invasions, colonization, globalization, and technological development have influenced the language. The conversation looks at present developments and potential future directions for English in the digital era.